2010
DOI: 10.1177/1321103x10370091
|View full text |Cite
|
Sign up to set email alerts
|

Peer assessment in tertiary level singing: Changing and shaping culture through social interaction

Abstract: In 2008, peer assessment was introduced into the singing component of a tertiary level undergraduate creative arts performance course within an Australian regional university. The study investigated what effect changing the role of the actor/singer in an assessment has on the culture of the course as well as individual development of graduate qualities, such as critical thinking and responsibility. It also looked at what process was involved in order to integrate peer assessment into the subject, and what kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…Charlotte was at first ostracised and belittled by her peers, potentially because the teachers had favourably singled her out. This peer approbation is what Kingsbury (1988) and Latukefu (2010) noted as being a potential hindrance to success for undergraduate musicians, along with the competitive atmosphere of conservatoria and in the music industry generally. Charlotte, however, eventually found a place and sense of belonging within the conservatorium as a “mentor” or “advisory” figure: That was pretty hard, but once the students got to know me … now I feel that we’ve come to a new phase where I sort of feel like the mother hen, you know and they come to me with their problems.…”
Section: Findings and Discussionmentioning
confidence: 89%
“…Charlotte was at first ostracised and belittled by her peers, potentially because the teachers had favourably singled her out. This peer approbation is what Kingsbury (1988) and Latukefu (2010) noted as being a potential hindrance to success for undergraduate musicians, along with the competitive atmosphere of conservatoria and in the music industry generally. Charlotte, however, eventually found a place and sense of belonging within the conservatorium as a “mentor” or “advisory” figure: That was pretty hard, but once the students got to know me … now I feel that we’ve come to a new phase where I sort of feel like the mother hen, you know and they come to me with their problems.…”
Section: Findings and Discussionmentioning
confidence: 89%
“…These studies did not involve music students, but the results have been substantiated for this student group as well. In a study on group teaching among tertiary voice students (Latukefu 2009(Latukefu , 2010, the students reported that taking part in peer assessment helped improve their own performance. In their discussion of the positive effects of peer assessment, Searby and Ewers (1997, 381) claim that students will develop a deeper and more critical understanding of musical performance and the processes involved when asked to assess fellow students; the learning goals will become clearer as they gain a better understanding of the assessment criteria.…”
Section: Issues To Be Discussedmentioning
confidence: 97%
“…Daniel (2004), Falchikov (2007), Lebler (2007) and Latukefu (2010), all emphasise that involvement in peer assessment, and thus improving the capacity for self-assessment, can help students to develop a sense of ownership of learning and a feeling of control of the learning process. Vocal/ instrumental tuition is often characterised as a type of master-apprentice relationship (Nielsen 1998;Burwell 2005;Nerland 2007;Gaunt, 2008;Gaunt et al 2012).…”
Section: Issues To Be Discussedmentioning
confidence: 97%
“…Latukefu (2010) examined a scaffolded peer-assessment framework among undergraduate vocal students at an Australian university. Adapting the model set by Searby and Ewers (1997), student focus groups established the assessment criteria and processes before the programme was implemented across a cohort.…”
Section: Introductionmentioning
confidence: 99%